Genotype-guided therapy improves initial acenocoumarol dosing - Cerezo-Manchado, Juan Jose; Roldán, Vanessa; Corral, Javier; Rosafalco, Mario; Antón, Ana Isabel; Padilla, Jose; Vicente, Vicente; González-Conejero, Rocio (Thrombosis and Haemostasis, 2016)
A few trials so far have evaluated the effectiveness of algorithms designed to calculate doses in oral anticoagulant therapy, with negative or contradictory results. We compared a genotype-guided algorithm vs physician management for the initiation of acenocoumarol. In a twoarm, prospective, randomised study with patients with atrial fibrillation who started therapy, the first dose was administered to all patients according to the physician’s criteria. At 72 hours, the corresponding dose was calculated based on INR in the standard care group (SC, N=92), whereas genetic data (VKORC1, CYP2C9 and CYP4F2) were also considered for the genotype-guided dosing (pharmacogenetic) group (PGx, N=87) by using an algorithm previously validated in 2,683 patients. The primary outcomes were: patients with steady dose, the time needed to reach the same and the percentage of therapeutic INRs. After 90 days, 25 % of the SC and 39 % of the PGx patients reached the steady dose (p=0.038). Kaplan-Meier analysis showed that PGx group needed fewer days to reach therapeutic INR (p=0.033). Additionally, PGx had a higher percentage of therapeutic INRs than SC patients (50 % and 45 %, respectively) (p=0.046). After six months the proportion of steadily anticoagulated patients remained significantly higher in PGx (p=0.010). In conclusion, genotype-guided dosing was associated with a higher percentage of patients with steady dose than routine practice when starting oral anticoagulation with acenocoumarol.
Keywords: Acenocoumarol; algorithm; cytochromes; pharmacogenetics; vitamin K epoxide reductase complex; subunit 1 protein; human